Potential Drug Interactions and Drug Risk during Pregnancy and Breastfeeding: An Observational Study in a Women's Health Intensive Care Unit - Ferracini, Amanda Canato; Rodrigues, Aline Teotonio; Visacri, Marília Berlofa; Stahlschmidt, Rebeca; Silva, Nice Maria Oliveira da; Surita, Fernanda Garanhani; Mazzola, Priscila Gava (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2017)
Introduction In the pregnancy-puerperal cycle, women may develop complications that require admission to the Intensive Care Unit (ICU). Thus, special attention to pharmacotherapy is necessary, particularly to potential drug interactions (PDIs) and to the effect of the drugs on the fetus and newborn.Objective The aim of this study was to determine the profile of PDIs and the potential risk of drugs used during pregnancy and breastfeeding among patients admitted to the ICU.Methods We conducted an observational, cross-sectional and prospective study, including pregnant and breastfeeding women admitted to the ICU at the Women's Hospital of a university in the city of Campinas, Brazil, for one year. Online databases were used to identify and classify the PDIs and the potential risk of the drugs used during pregnancy and breastfeeding.Results We evaluated 305 prescriptions of 58 women, 31 pregnant and 27 breastfeeding, and 284 (91%) prescriptions presented PDIs. A total of 175 different combinations of PDIs were identified in the prescriptions, and adverse effects caused by the simultaneous use of drugs were not actually observed in the clinical practice. A total of 26 (1.4%) PDIs were classified as contraindicated. We identified 15 (13.8%) drugs prescribed with risk D, and 2 (1.8%) with risk X for pregnant women, as well as 4 (4.9%) drugs prescribed with high risk for breastfeeding women.Conclusions This study demonstrates that there is a high incidence of PDIs in prescriptions. Most drugs used by pregnant and breastfeeding women at the ICU did not present serious risks to their fetus and newborns, but sometimes drugs with risk D or X are necessary in the course of the treatment.Introdução No ciclo gravídico-puerperal, as mulheres podem desenvolver complicações que necessitam de internação na Unidade de Terapia Intensiva (UTI). Assim, é necessária uma atenção especial à farmacoterapia, particularmente às interações medicamentosas potenciais (IMPs) e ao risco dos medicamentos para o feto e o recém-nascido.Objetivo Determinar o perfil das IMPs e o risco potencial dos medicamentos utilizados durante a gravidez e a amamentação entre as mulheres internadas em UTI.Métodos Foi realizado um corte transversal e prospectivo, observacional, incluindo mulheres grávidas e lactantes internadas na UTI do Hospital da Mulher de uma universidade de Campinas durante um ano. Bases de dados online foram usadas para identificar e classificar as IMPs e o potencial risco de uso de medicamentos durante a gravidez e a amamentação.Resultados Foram avaliadas 305 prescrições de 58 mulheres, 31 grávidas e 27 lactantes, e 284 (91%) prescrições apresentaram IMPs, sendo que 175 combinações diferentes de IMPs foram identificadas nas prescrições, e não foram observados efeitos nocivos pelo uso concomitante dos medicamentos na prática clínica. Um total de 26 (1,4%) IMPs foram classificadas como contraindicadas. Foram identificados 15 (13,8%) medicamentos prescritos com risco D, e 2 (1,8%) com risco X para mulheres grávidas, e foram identificados 4 (4,9%) medicamentos prescritos como de alto risco para as mulheres que estavam amamentando.Conclusões Este estudo demonstra que há uma alta incidência de IMPs nas prescrições. A maioria dos medicamentos utilizados por mulheres grávidas e lactantes em UTI não apresentou sérios riscos para o feto e o recém-nascido, mas às vezes são necessários medicamentos categorizados como risco D ou X.
Keywords: intensive care unit; potencial drug interactions; pregnancy; breastfeeding; patient safety